A critical discourse analysis of global economy in strategic texts / Mustafa - Mustafa, M. (2014)
A contentious question in critical discourse analysis has been whether and how ideology is embedded in discourse. This question has attracted attention from scholars within humanities and social sciences. A number of scholars argue that there is a dialectical relationship between discourse and ideology. Discourse internalizes and is internalized. By referring to discourse analysis as an explanatory critique, this study examines the discursive strategies in ideological construction of global economy in strategic texts. A discursive strategy is defined as the tool by which a discourse is given meaning and force and through which its object is described. It is a device by which ideology about the object is instilled in discourse and a means by which the agency and state are constituted. A strategic text is a discourse type that dominates the ways of representing the social issues, such as free market and trade liberalization. It discursively inculcates ideology, internalizes values, establishes social relations, and constructs identity. The strategic texts referred in this study are newspaper Opinion-Editorials and political speeches. This study examines the discursive strategies from the lens of ideological and identity construction and the desirable values of global economy in the strategic texts. The main objective of study is to analyze how an author—defined as a writer or speaker who textures texts—discursively constructs global economy in the strategic texts and to uncover what ideology and identity are embedded in those texts. The theoretical framework for the study is built upon a transdisciplinary approach to global economy that comprises theories of globalization, theories of discourse and ideology, and theories of discourse as a facet of globalization as articulated in the field of critical discourse analysis. iv The main sources of data were collected from Opinion-Editorials of two widely circulated newspapers—the Washington Post and the China Daily—and speeches by political figures and economists, George Bush, Barrack Obama, Ben Bernanke, Frederic Mishkin, Wen Jiabao, and Zeng Peiyan. The data consist of 14 newspaper Opinion-Editorials and six speeches. 10 texts represent the USA and the other 10 represents China. These typical strategic texts on the global economy appeared between 2005 and 2011. The method of analysis is critical discourse analysis in which a set of developed analytical tools is used for analyzing text extracts. The analysis shows that the discourse of global economy in the strategic texts is constructed through universalization and naturalization of the political economy systems that global economy is inevitability and inexorableness. The authors construct these systems through a mixture of textual processes. The most apparent discursive strategies of internalizing these systems are vocabulary and argumentation. The analysis also reveals that the discourse of global economy is not ideology-free. The analysis of extracts indicates that the strategic texts construct the ideologies of capitalism and new capitalism. The social identity of the authors and national identity are embedded in the discourse of global economy. Five major desirable elements in the discourse of global economy are identified: increased flows of capital and investment, competition in global marketplace, scaling economic programs, restructuring economic practices, and deregulation of trade. The genres and discourses are networked together in the global economic texts. The analysis of the U.S. and China’s views on the global economy shows that the U.S economic system is built upon Western liberal capitalism while China has moved from communism to state capitalism with Asian values. Although the two countries endorse free market capitalism, China has currently been an economic threat to the USA. The practices of free market capitalism have discursively given rise to the global financial crisis and war on currency. v Global economic programs can be both realities and imaginaries. The world society thus should acclimatize the real programs, but needs to transform and emancipate the ones that are incompatible with the discursive practices of global economy to create the well-being of nations through equity of social changes. For that reason, there should be a critical awareness-raising program for the society on the importance of understanding both the discursive processes and the material processes of global economy. This can be done by incorporating critical language awareness into globalization studies within an institutional system of higher education.